Carbohydrate Coatings via Aryldiazonium Chemistry for Surface Biomimicry - Colavita, Paula (My University, 2013)
Carbohydrates are extremely important biomolecules and their immobilization onto solid surfaces is of interest for the development of new biomimetic materials and of new methods for understanding processes in glycobiology. We have developed an efficient surface modification methodology for the functionalization of a range of materials with biologically active carbohydrates based on aryldiazonium chemistry. We describe the synthesis and characterization of carbohydrate reagents, which were subsequently employed for the one-step, solution-based modification of carbon, metals, and alloys with monosaccharides. We used a combination of spectroscopic and nanogravimetric methods to characterize the structure of the carbohydrate layers; we report an average surface coverage of 7.8 × 10–10 mol cm–2 under our experimental conditions. Concanavalin A, a mannose-binding lectin, and Peanut Agglutinin, a galactose-binding lectin, were found to bind from solution to their respective monosaccharide binding partners immobilized at the surface. This result suggests that the spontaneous chemisorption of aryldiazonium monosaccharide precursors leads to the formation of monosaccharide layers that retain the biological recognition specificity of the parent carbohydrate molecule. Finally, we carried out measurements using fluorescently labeled Bovine Serum Albumin (BSA) and found that these carbohydrate coatings reduce unspecific adsorption of this protein at carbon surfaces. These results suggest that aryldiazonium-derived carbohydrate coatings may offer a promising strategy for preventing undesirable protein accumulation onto surfaces.
PUBLISHED
Keywords: Carbohydrate; Saccharide; Diazonium; Carbon; Coatings